Flaxseed-Based Drug Delivery Systems: Advancing Colon Cancer Treatment - Mohd.Wasiullah; Piyush Yadav; Mohit Vishwakarma; Nidhi Dubey (Emerging Trends in Personalized Medicines, 2025)
Flaxseed (Linum usitatissimum) has long been appreciated for its rich nutritional profile, including essential fatty acids (such as α-linolenic acid), plant fibers, and lignans. Recent research has focused on its potential as a novel drug delivery system (DDS) for the treatment of colon cancer. This review explores the bioactive constituents of flaxseed, their pharmacological activities, and innovative approaches to the use of flaxseed extracts in drug delivery for the treatment of colon cancer. We highlight the promising pharmacokinetics, target delivery mechanisms, and therapeutic efficacy of flaxseed drug carriers, as well as challenges and future directions in the field. One of the main causes of cancer-related fatalities, colon cancer is a serious worldwide health concern. Effective drug delivery systems (DDS) are essential to target the disease while minimizing systemic toxicity. Flax, a natural product rich in lignans, omega-3 fatty acids, and fiber, has shown promise in cancer treatment due to its anti-inflammatory, antioxidant, and anticarcinogenic properties. This paper investigates the potential of flax extract as a novel drug delivery system (NDDS) for the targeted delivery of chemotherapeuticagents to colon cancer cells. We explore the bioactive compounds of flaxseed, their interactions with drug molecules, and the use of flax-based DDS to improve the bioavailability and therapeutic efficacy of anticancer drugs.
Keywords: Colon cancer; Linum usitatissimum; Pharmacokinetics of flax-based DDS; Targeted therapy; flaxseed